Art for every home: an illustrated index of Associated American Artists prints, ceramics, and textile designs - Windisch, Gail; Cole, Sylvan; Herbaugh, Karen J. (Marianna Kistler Beach Museum of Art. Kansas State University. Manhattan, Kansas., 2015)
Art for Every Home: An Illustrated Index of Associated American Artists Prints, Ceramics, and Textile Designs is the digital companion to Art for Every Home: Associated American Artists (2015), the catalogue that accompanies the traveling exhibition of the same name organized by the Marianna Kistler Beach Museum of Art, Kansas State University, Manhattan. The exhibition and catalogue provide the first comprehensive and critical overview of Associated American Artists (AAA), including its innovative and far-reaching promotion of artists’ work from the mid- 1930s to the early 1980s. To augment and amplify the exhibition’s presentation of the business, this digital publication provides illustrated comprehensive indexes of AAA prints, ceramics, textile designs, and sales materials, as well as a list of exhibitions held at the AAA galleries.
For inquiries, please reach out to the Marianna Kistler Beach Museum of Art. beachart@ksu.edu